IACME and Mathematics Education International Organizations in Latin America - Ruiz, Angel (Universidad de Costa Rica, 2014)
The evolution of the Inter-American Committee on Mathematics Education (IACME) as a network of regional and international cooperation will be described, as well as -with less detail- the Latin American Committee on Educational Mathematics (CLAME) and the Ibero-American Federation of Educational Mathematics (FISEM), and the Mathematics Education Network for Central America and Caribbean (RE- DUMATE). Emphasis will be placed on the overall meaning of their academic and organizational evolution. In particular, the relationships of IACME with the In- ternational Commission on Mathematical Instruction (ICMI) and the international community of Mathematics Education will be analyzed. Some perspectives will be considered.